Forest regeneration management and policy in the Nordic–Baltic region since 1900. Issue 7 (17th November 2021) - Girdziušas, Sigitas; Löf, Magnus; Hanssen, Kjersti Holt; Lazdiņa, Dagnija; Madsen, Palle; Saksa, Timo; Liepiņš, Kaspars; Fløistad, Inger Sundheim; Metslaid, Marek
ABSTRACT : Since the beginning of the twentieth century, forest regeneration management and policy in the Nordic–Baltic region (Denmark, Sweden, Norway, Finland, Estonia, Latvia and Lithuania) have gone through significant changes. For decades forest as a key natural resource was managed with main focus on timber production. However, several factors influenced shifting forest management, including forest regeneration to meet a wide range of society needs. This review study aims to reveal the historical development of forest regeneration identifying knowledge gaps and supporting decisions that promote sustainable regeneration of future forests. The development of forest regeneration management and policy in the Nordic–Baltic countries is analyzed through reforestation and afforestation practices as well as legislation aspects using a narrative review approach. Trends in forest regeneration practices within the region are identified and explored over a timeframe spanning from 1900 until today. Despite diverse forestry management structures and differing political, social situations, the study shows that forest regeneration development has followed similar patterns over time in all Nordic–Baltic region countries: extensive forestry, clear-cut forestry, retention forestry and currently evolving climate-adaptive forestry. Nevertheless, regional differences among the Nordic–Baltic countries, especially in forest regeneration-related legislation, were identified due to a mixture of international and local driving forces.